THE EFFORT OF THE PATROL UNIT OF THE SAMAPTA UNIT TO PREVENT THE CRIMINAL ACTION OF THE WEIGHTING WITH THE WEALING OF THE KARANGANYAR POLICE LAWS - steven rumapea (Indonesian Journal of Police Studies, 2022)
ABSTRACT THE EFFORT OF THE PATROL UNIT OF THE SAMAPTA UNIT TO PREVENT THE CRIMINAL ACTION OF THE WEIGHTING WITH THE WEALING OF THE KARANGANYAR POLICE LAWS Steven Leonard rumapea,No.Ak.18.188,stevenrumapea91@gmail.com This research is motivated by the high number of criminal acts of theft by weighting (curat) in Karanganyar Regency. As a crime prevention measure, the Samapta patrol unit plays a major role in this problem. This study aims to analyze the efforts of the Sabhara unit patrol in preventing the crime of theft by weighting, the factors that affect the implementation of the Samapta unit patrol and the implementation of patrols in preventing the crime of theft with the weight itself. This research was conducted using a qualitative approach and data collection techniques by interview, observation, and document study. From this research, it can be seen that there is a real picture of the prevention efforts carried out by the Karanganyar Police Samapta unit against the crime of stealing. To process the data obtained by researchers using management theory, Perkabaharkam Number 1 of 2017 concerning Patrols and the Promoter concept launched by the National Police Chief. The results of the study found that the patrol efforts of the Samapta unit had not been fulfilled optimally because management had problems in the aspects of preparation, organization, movement, and control. This is influenced by several inhibiting factors, namely internal factors and external factors. Based on the results of the study, the authors suggest eliminating the negative work culture in the Samapta unit, implementing patrol strategies in accordance with Perkabaharkam Number 1 of 2017 concerning Patrols, it is necessary to control patrol activities as well as equal distribution of personnel placement and special training in patrol skills. Thus the patrol efforts of the Karanganyar Police Sabhara unit in preventing the crime of stealing can be fulfilled optimally.